The ability of mathematical problem solving reviewed from goal orientation to learning model of problem based learning assisted by problem card - Mulyono, Mulyono; Rahma Wati, Meca Indah; Amidi, Amidi (Unnes Journal of Mathematics Education, 2019)
The aims of this study are to prove the problem solving abilities of students in the application of Problem based learning (PBL) models assisted by problem cards to achieve classical completeness. The research used mixed method. The sample in this study were students of class VII D and VII E. Quantitative data was done by simple random sampling technique. Quantitative data was obtained using tests. Qualitative data analysis is the analysis of interview data. The results showed that (1) problem solving ability of 7th grade students achieving classical completeness; (2) problem solving abilities of students with PBL models assisted by problem cards reach the Minimum Completeness Criteria; (3) the proportion test results of students' in experimental class is better than students in control class. (4) the average test results of students in experimental class are better than the average results of students in control clas; (5) students in the mastery goal group meet the indicators of problem solving abilities while the students in the performance goal group have not met the indicators of problem solving abilities